Translating the Dressing Code: A Semiotic Approach of Fashion in Barva, Heredia - Hernández Ching, Ruth Cristina (2025)
The purpose of this essay is to breathe new life into the textile industry in Barva, Heredia, Costa Rica, not only from the semiotic perspective but also as a formative activity. After making a bibliography review of the previously published, there are no similar investigations. Then, a qualitative research is chosen, compiling the experience of personal lives in relation to the activity. It is concluded that this activity made them to have a better standard of living.